Implementações Eficientes da Heurística Min-Min para o HCSP em GPU - Schmid, Rafael F.; Cáceres, Edson N. (Anais do Encontro de Teoria da Computação (ETC); 2018: Anais do III Encontro de Teoria da ComputaçãoDO - 10.5753/etc.2018.3156, 2018)
Min-min heuristic is one of the most indicated algorithm to solve HCSP, when we are looking for performance. A previous result presented an efficient implementation to this problem with assymptotic complexity O(t log(t)m). In this work, we implement this problem with linear complexity. Our implementation is competitive with the previous results.